PENGARUH KOMBINASI PAKAN ALTERNATIF DENGAN PERSENTASE YANG BERBEDA TERHADAP TINGKAT KELANGSUANG HIDUP DAN PERTUMBUHAN BENIH LOBSTER AIR TAWAR (Cherax quadricarinatus) DI UPR KURNIA KABUPATEN MAROS - Aminuddin Aminuddin; Riskayanti Riskayanti; Takdir Takdir; Risqah Amaliah Kasman; St. Rhodiatul Aisyah Ramadhani; Sumardi Sumardi (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
Freshwater lobster (Cherax quadricarinatus) is a high-value aquaculture commodity with rapid growth and strong adaptability. However, the high cost of feed—accounting for 60–70% of total production expenses—remains a major constraint for farmers. The use of alternative plant–animal feed combinations offers a potential solution to reduce production costs without compromising nutritional quality. This study aims to analyze the effect of different proportions of alternative feed combinations on the absolute weight gain of freshwater lobster juveniles, determine the most optimal feed composition, describe growth patterns, and evaluate water quality as a supporting factor. The research was conducted for four weeks using an experimental method with a Completely Randomized Design (CRD) consisting of five treatments and five replications. The results showed that feed combinations had a highly significant effect on growth. Treatment D (25% plant-based + 75% animal-based feed) produced the highest absolute weight gain of 10 g, indicating that animal protein plays a dominant role, while plant-based nutrients remain essential for balanced nutrition. Overall, plant–animal alternative feed combinations effectively enhanced the growth of freshwater lobster juveniles and present a cost-efficient alternative to commercial feed for farmers.